(untitled) (Asian Journal of Social Science Studies, 2022)
The Mid-Tang literature is an important stage in the literary history of the Tang Dynasty, and presents another high point in the creation of poetry after the flourishing Tang Dynasty, which is also known as the mid-emergence stage in the development of Tang literature. During the Yuanhe to Huichang periods, the literati living in Luoyang often gathered together to create and interact with poetry. The bureaucrats and scribes who lived in Luoyang were the mainstay of poetry writing. The bureaucrats and scribes who lived in Luoyang were the mainstay of poetry writing. They were both prominent politicians and literary leaders, but at a time of political turmoil and fierce party rivalry, they had no way out politically and had to seek a “retreat” from their career and literary expression. The Confucian scribes who were in close proximity to the bureaucratic scribes had lofty goals but unfortunate careers. With its outstanding geographical and cultural advantages, Luoyang provided favourable conditions for the gathering of bureaucratic scribes and for literary creation. It was of great importance in the development and formation of the poetic style of the Mid-Tang. This article examines the poetry of the bureaucratic scribes who lived in Luoyang during the Yuanhe to Huichang periods of the Tang Dynasty within the context of the city‟s spatial form. Firstly, the historical transmutation of the geospatial form of the city of Luoyang is explained. Then, from the perspective of public architecture landscape, it explores the emotional experience and spiritual sustenance of bureaucratic scribes to Luoyang urban landscape. It examines the dynamic interaction between the internal architecture of Luoyang City and the literary milieu of the middle Tang Dynasty.